A copper-aluminum alloy fin tube and its production process
By using a combination design of a fin tube body with a specific component and a functional coating on the copper-aluminum alloy fin tube, the existing copper-aluminum alloy fin tube has been solved, and the existing copper-aluminum alloy fin tube has low thermal efficiency, corrosion resistance and insufficient mechanical and mechanical properties when used in high-temperature and high-pressure corrosive atmospheres is achieved, and the copper-aluminum alloy fin tube and its production process are achieved.
Patent Information
- Application Number
- CN202410454855.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-04-16
AI Technical Summary
When used in high-temperature and high-pressure corrosive atmospheres, existing copper-aluminum alloy finned tubes have low thermal conductivity, insufficient corrosion resistance and mechanical and mechanical properties, resulting in short service life.
The design is adopted to combine the copper-aluminum alloy finned tube body with functional coating. The finned tube body is composed of specific components and is coated with functional coatings of materials such as nanoboron fibers, nanoboron nitride and nanotantalum silicide. Through mutual cooperation, the thermal conductivity, mechanical and mechanical properties and corrosion resistance are improved.
It significantly improves the thermal conductivity, mechanical and fatigue resistance of copper-aluminum alloy finned tubes, enhances corrosion resistance, extends service life, and is simple in process and low in energy consumption, making it suitable for industrial production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heat exchangers and relates to a heat exchanger component, in particular to a copper-aluminum alloy fin tube and a production process thereof. Background Art
[0002] Finned tubes are a type of heat exchange element, which is mainly used to improve heat exchange efficiency. Fins are usually added to the surface of the heat exchange tube to increase the outer surface area (or inner surface area) of the heat exchange tube, thereby achieving the purpose of improving heat exchange efficiency. Although finned tubes have the function of enhancing heat transfer, as heat exchange elements, they work under high-temperature flue gas conditions for a long time. For example, the finned tubes used in boiler heat exchangers are used in harsh environments, with high temperature, high pressure and in a corrosive atmosphere. If the finned tubes are in a harsh environment for a long time, their aging speed will be accelerated, affecting the thermal conductivity of the finned tubes. The thermal conductivity of the finned tubes affects the cooling effect of the heat exchange tubes. It can be seen that it is necessary to seek more suitable finned tube materials to improve the thermal conductivity and corrosion resistance of the finned tubes, thereby extending their service life.
[0003] Copper-aluminum alloy is widely used in the production of finned tubes because of its good mechanical properties, corrosion resistance and heat transfer performance. However, due to the unreasonable selection of composition formula, the existing copper-aluminum alloy finned tubes still have technical defects such as being greatly affected by the environment, low thermal conductivity, and corrosion resistance and mechanical properties need to be further improved. In order to solve the above problems, the Chinese invention patent with authorization announcement number CN105758244B discloses a copper-aluminum alloy base tube finned tube, the finned tube includes a base tube and a transverse fin arranged on the base tube, and the material of the base tube is copper-aluminum alloy. The mass percentage of the components of the copper-aluminum alloy is as follows: 3.7% Cr, 3.3% Ag, 2.2% Mn, 1.25% Zr, 1.23% Ce, 1.25% Ti, 2.46% Si, and the rest are Cu and Al, and the ratio of Cu to Al is (8.53-10.23): 1.12. The copper-aluminum alloy finned tube involved in the invention claims that it can not only meet the function of enhancing heat transfer, but also greatly increase the heat resistance of the alloy. However, its mechanical properties, thermal conductivity and fatigue resistance still need to be further improved.
[0004] It can be seen that how to provide a copper-aluminum alloy fin tube with good thermal conductivity, good mechanical properties and fatigue resistance, and excellent corrosion resistance and its production process is a difficult problem that researchers in the industry urgently need to solve. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a copper-aluminum alloy fin tube with good thermal conductivity, good mechanical properties and fatigue resistance, and excellent corrosion resistance, and a production process thereof.
[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a copper-aluminum alloy fin tube, comprising a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: Mo 0.5-1.5wt%, Ag 0.01-0.03wt%, Nb 0.1-0.3wt%, Co 0.2-0.6wt%, Hf 0.1-0.3wt%, rare earth elements 0.05-0.15wt%, Ni 0.01-0.12wt%, Zn 0.3-0.5wt%, Si 0.3-0.6wt%, Be0.005-0.015wt%, In0.003-0.01wt%, Na 0.001-0.003wt%, Al 8-15wt%, nano-boron fiber 0.01-0.03wt%, nano-boron nitride 0.01-0.03wt%, nano-tantalum silicide 0.005-0.012wt%, and the balance is Cu.
[0007] Preferably, the thickness of the functional coating is 50-100 microns.
[0008] Preferably, the rare earth element is a mixture of Sc, Y, La, and Ce in a mass ratio of 1:(1-2):(0.8-1.2):(1-1.5).
[0009] Preferably, the average diameter of the nano-boron fiber is 30-100 nm, and the aspect ratio is (15-25):1.
[0010] Preferably, the particle size of the nano boron nitride is 10-90 nm; the particle size of the nano tantalum silicide is 20-80 nm.
[0011] Preferably, the functional coating is made of the following components calculated in parts by weight: 40-50 parts of amino-terminated hyperbranched polysiloxane HPSi-NH2, 3-5 parts of 1,3,5-triglycidyl-S-triazinetrione, 10-15 parts of thermally conductive filler, 1-3 parts of coupling agent, 3-5 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 4-6 parts of 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione, and 60-80 parts of solvent.
[0012] Preferably, the amino-terminated hyperbranched polysiloxane HPSi-NH2 is prepared according to the method of Example 1 in the authorization publication number CN110156948B.
[0013] Preferably, the solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.
[0014] Preferably, the thermally conductive filler is at least one of aluminum nitride, boron nitride and silicon carbide; and the particle size of the thermally conductive filler is 1200-1600 mesh.
[0015] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0016] Another object of the present invention is to provide a production process of the copper-aluminum alloy fin tube, comprising the following steps:
[0017] Step S1, vacuum metallurgy smelting, argon protection casting into a round billet, after homogenization treatment, hot extrusion into a rod, and then heat treatment to obtain a fin tube body;
[0018] Step S2: after mixing the components of the functional coating evenly, apply the mixture on the surface of the fin tube body, and dry at 105-115° C. to a constant weight to obtain a copper-aluminum alloy fin tube.
[0019] Preferably, the temperature of the homogenization treatment in step S1 is 800-830°C for 1-2h; and the temperature of the hot extrusion is 630-650°C.
[0020] Preferably, the heat treatment in step S2 includes solution treatment, aging treatment and annealing treatment.
[0021] Preferably, the temperature of the solution treatment is 550-580°C, and the time is 3-5h; the temperature of the aging treatment is 190-240°C, and the time is 4-6h; the annealing treatment is 630-730°C, and the time is 2-4h.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The production process of the copper-aluminum alloy finned tube disclosed in the present invention can be realized by conventional operation and equipment, has low energy consumption, small capital investment, high production efficiency and finished product qualification rate, convenient operation and control, low labor intensity, small impact on the environment, and is suitable for industrial production.
[0024] (2) The copper-aluminum alloy fin tube disclosed in the present invention comprises a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: Mo 0.5-1.5wt%, Ag 0.01-0.03wt%, Nb0.1-0.3wt%, Co 0.2-0.6wt%, Hf 0.1-0.3wt%, rare earth elements 0.05-0.15wt%, Ni 0.01-0.12wt%, Zn0.3-0.5wt%, Si 0.3-0.6wt%, Be 0.005-0.015wt%, In 0.003-0.01wt%, Na0.001-0.003wt%, Al 8-15wt%, nano boron fiber 0.01-0.03wt%, nano boron nitride 0.01-0.03wt%, nano tantalum silicide 0.005-0.012wt%, and the balance is Cu. Through the mutual cooperation between the components, the copper-aluminum alloy fin tube has good thermal conductivity, good mechanical properties and fatigue resistance, and excellent corrosion resistance. The combination of nano boron fiber, nano boron nitride and nano tantalum silicide can not only improve the mechanical properties through the dispersion strengthening mechanism, but also improve the thermal conductivity, and cooperate with other components to improve the corrosion resistance and fatigue resistance.
[0025] (3) The copper-aluminum alloy fin tube disclosed in the present invention, the functional coating is made of the following components calculated by weight: 40-50 parts of terminal amino hyperbranched polysiloxane HPSi-NH2, 3-5 parts of 1,3,5-triglycidyl-S-triazinetrione, 10-15 parts of thermal conductive filler, 1-3 parts of coupling agent, 3-5 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 4-6 parts of 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione, and 60-80 parts of solvent. Through the mutual coordination between the components, the thermal conductivity and corrosion resistance of the product can be effectively improved. At the same time, the hyperbranched polysiloxane structure, triazone structure, fluorinated phenyl ether structure and imidazolidone structure introduced can further improve the corrosion resistance and thermal conductivity of the coating under the multiple effects of electronic effect, steric effect and conjugation effect, and improve the adhesion between the coating and the body, thereby improving the comprehensive performance and performance stability of the product; in addition, the amino-containing components in the functional coating will undergo epoxy ring-opening reaction with the epoxy-containing components to form an interpenetrating network structure, improve the density of the coating, and form more effective thermal bridges, thereby improving the thermal conductivity, performance stability and corrosion resistance of the material.
[0026] (4) The copper-aluminum alloy fin tube disclosed in the present invention has better thermal conductivity, better mechanical properties and fatigue resistance, and better corrosion resistance through reasonable selection of preparation process parameters. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0028] Example 1
[0029] A copper-aluminum alloy fin tube comprises a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: Mo 0.5wt%, Ag 0.01wt%, Nb 0.1wt%, Co 0.2wt%, Hf 0.1wt%, rare earth elements 0.05wt%, Ni 0.01wt%, Zn 0.3wt%, Si 0.3wt%, Be 0.005wt%, In 0.003wt%, Na 0.001wt%, Al 8wt%, nano-boron fiber 0.01wt%, nano-boron nitride 0.01wt%, nano-tantalum silicide 0.005wt%, and the balance is Cu.
[0030] The thickness of the functional coating is 60 microns; the rare earth elements are a mixture of Sc, Y, La, and Ce in a mass ratio of 1:1:0.8:1; the average diameter of the nano-boron fiber is 30nm, and the aspect ratio is 15:1; the particle size of the nano-boron nitride is 10nm; and the particle size of the nano-tantalum silicide is 20nm.
[0031] The functional coating is made of the following components calculated in parts by weight: 40 parts of amino-terminated hyperbranched polysiloxane HPSi-NH2, 3 parts of 1,3,5-triglycidyl-S-triazinetrione, 10 parts of thermally conductive filler, 1 part of coupling agent, 3 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 4 parts of 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione, and 60 parts of solvent; the amino-terminated hyperbranched polysiloxane HPSi-NH2 is made according to the method of Example 1 in the authorization announcement number CN110156948B; the solvent is N,N-dimethylacetamide; the thermally conductive filler is aluminum nitride; the particle size of the thermally conductive filler is 1200 mesh; and the coupling agent is silane coupling agent KH550.
[0032] A production process of the copper-aluminum alloy fin tube comprises the following steps:
[0033] Step S1, vacuum metallurgy smelting, argon protection casting into a round billet, after homogenization treatment, hot extrusion into a rod, and then heat treatment to obtain a fin tube body;
[0034] Step S2: after mixing the components of the functional coating evenly, apply the mixture on the surface of the fin tube body, and dry at 105-115° C. to a constant weight to obtain a copper-aluminum alloy fin tube.
[0035] The temperature of the homogenization treatment in step S1 is 800°C and the time is 1h; the temperature of the hot extrusion is 630°C; the heat treatment in step S2 includes solution treatment, aging treatment and annealing treatment; the temperature of the solution treatment is 550°C and the time is 3h; the temperature of the aging treatment is 190°C and the time is 4h; the annealing treatment is 630°C and the time is 2h.
[0036] Example 2
[0037] A copper-aluminum alloy fin tube comprises a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: Mo 0.7wt%, Ag 0.015wt%, Nb 0.15wt%, Co 0.3wt%, Hf 0.15wt%, rare earth elements 0.07wt%, Ni 0.04wt%, Zn 0.35wt%, Si 0.4wt%, Be 0.007wt%, In 0.005wt%, Na 0.0015wt%, Al 10wt%, nano-boron fiber 0.015wt%, nano-boron nitride 0.015wt%, nano-tantalum silicide 0.007wt%, and the balance is Cu.
[0038] The thickness of the functional coating is 60 microns; the rare earth elements are a mixture of Sc, Y, La, and Ce in a mass ratio of 1:1.2:0.9:1.2; the average diameter of the nano-boron fiber is 50nm, and the aspect ratio is 18:1; the particle size of the nano-boron nitride is 30nm; and the particle size of the nano-tantalum silicide is 40nm.
[0039] The functional coating is made of the following components calculated in parts by weight: 43 parts of amino-terminated hyperbranched polysiloxane HPSi-NH2, 3.5 parts of 1,3,5-triglycidyl-S-triazinetrione, 12 parts of thermal conductive filler, 1.5 parts of coupling agent, 3.5 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 4.5 parts of 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione, and 65 parts of solvent.
[0040] The amino-terminated hyperbranched polysiloxane HPSi-NH2 is prepared according to the method of Example 1 in the authorization announcement number CN110156948B; the solvent is N,N-dimethylformamide; the thermal conductive filler is boron nitride; the particle size of the thermal conductive filler is 1300 mesh; and the coupling agent is silane coupling agent KH560.
[0041] A production process of the copper-aluminum alloy fin tube comprises the following steps:
[0042] Step S1, vacuum metallurgy smelting, argon protection casting into a round billet, after homogenization treatment, hot extrusion into a rod, and then heat treatment to obtain a fin tube body;
[0043] Step S2: after mixing the components of the functional coating evenly, apply the mixture on the surface of the fin tube body, and dry the mixture at 108° C. to a constant weight to obtain a copper-aluminum alloy fin tube.
[0044] The temperature of the homogenization treatment in step S1 is 810°C and the time is 1.2h; the temperature of the hot extrusion is 635°C; the heat treatment in step S2 includes solution treatment, aging treatment and annealing treatment; the temperature of the solution treatment is 560°C and the time is 3.5h; the temperature of the aging treatment is 200°C and the time is 4.5h; the annealing treatment is 650°C and the time is 2.5h.
[0045] Example 3
[0046] A copper-aluminum alloy fin tube comprises a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: 1wt% Mo, 0.02wt% Ag, 0.2wt% Nb, 0.4wt% Co, 0.2wt% Hf, 0.1wt% rare earth element, 0.08wt% Ni, 0.4wt% Zn, 0.45wt% Si, 0.01wt% Be, 0.006wt% In, 0.002wt% Na, 12wt% Al, 0.02wt% nano-boron fiber, 0.02wt% nano-boron nitride, 0.008wt% nano-tantalum silicide, and the balance is Cu.
[0047] The thickness of the functional coating is 60 microns; the rare earth elements are a mixture of Sc, Y, La, and Ce in a mass ratio of 1:1.5:1:1.2; the average diameter of the nano-boron fiber is 75nm, and the aspect ratio is 20:1; the particle size of the nano-boron nitride is 60nm; and the particle size of the nano-tantalum silicide is 60nm.
[0048] The functional coating is made of the following components calculated in parts by weight: 45 parts of amino-terminated hyperbranched polysiloxane HPSi-NH2, 4 parts of 1,3,5-triglycidyl-S-triazinetrione, 13 parts of thermally conductive filler, 2 parts of coupling agent, 4 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 5 parts of 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione, and 70 parts of solvent; the amino-terminated hyperbranched polysiloxane HPSi-NH2 is made according to the method of Example 1 in the authorization announcement number CN110156948B; the solvent is N-methylpyrrolidone; the thermally conductive filler is silicon carbide; the particle size of the thermally conductive filler is 1400 mesh; and the coupling agent is silane coupling agent KH570.
[0049] A production process of the copper-aluminum alloy fin tube comprises the following steps:
[0050] Step S1, vacuum metallurgy smelting, argon protection casting into a round billet, after homogenization treatment, hot extrusion into a rod, and then heat treatment to obtain a fin tube body;
[0051] Step S2: after mixing the components of the functional coating evenly, apply the mixture on the surface of the fin tube body, and dry the mixture at 110° C. to a constant weight to obtain a copper-aluminum alloy fin tube.
[0052] The temperature of the homogenization treatment in step S1 is 815°C and the time is 1.5h; the temperature of the hot extrusion is 640°C; the heat treatment in step S2 includes solution treatment, aging treatment and annealing treatment; the temperature of the solution treatment is 565°C and the time is 4h; the temperature of the aging treatment is 220°C and the time is 5h; the annealing treatment is 690°C and the time is 3h.
[0053] Example 4
[0054] A copper-aluminum alloy fin tube comprises a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: Mo 1.3wt%, Ag 0.025wt%, Nb 0.25wt%, Co0.5wt%, Hf0.25wt%, rare earth elements 0.13wt%, Ni 0.1wt%, Zn 0.45wt%, Si 0.55wt%, Be0.013wt%, In0.008wt%, Na 0.0025wt%, Al 13wt%, nano-boron fiber 0.025wt%, nano-boron nitride 0.025wt%, nano-tantalum silicide 0.01wt%, and the balance is Cu.
[0055] The thickness of the functional coating is 60 microns; the rare earth elements are a mixture of Sc, Y, La, and Ce in a mass ratio of 1:1.8:1.1:1.4; the average diameter of the nano-boron fiber is 90nm, and the aspect ratio is 23:1; the particle size of the nano-boron nitride is 80nm; and the particle size of the nano-tantalum silicide is 70nm.
[0056] The functional coating is made of the following components calculated by weight: 48 parts of amino-terminated hyperbranched polysiloxane HPSi-NH2, 4.5 parts of 1,3,5-triglycidyl-S-triazinetrione, 14 parts of thermal conductive filler, 2.5 parts of coupling agent, 4.5 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 5.5 parts of 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione, and 75 parts of solvent; the amino-terminated hyperbranched polysiloxane HPSi-NH2 is It is prepared according to the method of Example 1 in the authorization announcement number CN110156948B; the solvent is a mixture of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone in a mass ratio of 1:2:3; the thermally conductive filler is a mixture of aluminum nitride, boron nitride, and silicon carbide in a mass ratio of 1:3:5; the particle size of the thermally conductive filler is 1500 mesh; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 1:3:3.
[0057] A production process of the copper-aluminum alloy fin tube comprises the following steps:
[0058] Step S1, vacuum metallurgy smelting, argon protection casting into a round billet, after homogenization treatment, hot extrusion into a rod, and then heat treatment to obtain a fin tube body;
[0059] Step S2: after mixing the components of the functional coating evenly, apply the mixture on the surface of the fin tube body, and dry the mixture at 113° C. to a constant weight to obtain a copper-aluminum alloy fin tube.
[0060] The temperature of the homogenization treatment in step S1 is 825°C and the time is 1.8h; the temperature of the hot extrusion is 645°C; the heat treatment in step S2 includes solution treatment, aging treatment and annealing treatment; the temperature of the solution treatment is 575°C and the time is 4.5h; the temperature of the aging treatment is 230°C and the time is 5.5h; the annealing treatment is 720°C and the time is 3.5h.
[0061] Example 5
[0062] A copper-aluminum alloy fin tube comprises a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: Mo 1.5wt%, Ag 0.03wt%, Nb 0.3wt%, Co 0.6wt%, Hf 0.3wt%, rare earth elements 0.15wt%, Ni 0.12wt%, Zn 0.5wt%, Si 0.6wt%, Be 0.015wt%, In 0.01wt%, Na 0.003wt%, Al 15wt%, nano-boron fiber 0.03wt%, nano-boron nitride 0.03wt%, nano-tantalum silicide 0.012wt%, and the balance is Cu.
[0063] The thickness of the functional coating is 60 microns; the rare earth elements are a mixture of Sc, Y, La, and Ce in a mass ratio of 1:2:1.2:1.5; the average diameter of the nano-boron fiber is 100 nm, and the aspect ratio is 25:1; the particle size of the nano-boron nitride is 90 nm; and the particle size of the nano-tantalum silicide is 80 nm.
[0064] The functional coating is made of the following components calculated in parts by weight: 50 parts of amino-terminated hyperbranched polysiloxane HPSi-NH2, 5 parts of 1,3,5-triglycidyl-S-triazinetrione, 15 parts of thermally conductive filler, 3 parts of coupling agent, 5 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 6 parts of 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione, and 80 parts of solvent; the amino-terminated hyperbranched polysiloxane HPSi-NH2 is made according to the method of Example 1 in the authorization announcement number CN110156948B; the solvent is N,N-dimethylformamide; the thermally conductive filler is boron nitride; the particle size of the thermally conductive filler is 1600 mesh; and the coupling agent is silane coupling agent KH560.
[0065] A production process of the copper-aluminum alloy fin tube comprises the following steps:
[0066] Step S1, vacuum metallurgy smelting, argon protection casting into a round billet, after homogenization treatment, hot extrusion into a rod, and then heat treatment to obtain a fin tube body;
[0067] Step S2: after mixing the components of the functional coating evenly, apply the mixture on the surface of the fin tube body, and dry at 105-115° C. to a constant weight to obtain a copper-aluminum alloy fin tube.
[0068] The temperature of the homogenization treatment in step S1 is 830°C and the time is 2h; the temperature of the hot extrusion is 650°C; the heat treatment in step S2 includes solution treatment, aging treatment and annealing treatment; the temperature of the solution treatment is 580°C and the time is 5h; the temperature of the aging treatment is 240°C and the time is 6h; the annealing treatment is 730°C and the time is 4h.
[0069] Comparative Example 1
[0070] A copper-aluminum alloy fin tube is substantially the same as Example 1, except that In, nano-tantalum silicide and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane are not added.
[0071] Comparative Example 2
[0072] A copper-aluminum alloy fin tube is substantially the same as Example 1, except that Co, Na, nano-boron nitride and 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione are not added.
[0073] In order to further illustrate the unexpected positive technical effects achieved by the copper-aluminum alloy fin tube products involved in each embodiment of the present invention, the copper-aluminum alloy fin tubes manufactured in each example are tested for relevant performances. The test results are shown in Table 1. The test method is as follows:
[0074] (1) Tensile strength: A room temperature tensile test was performed according to GB / T228.1-2010 to measure the tensile strength of the copper-aluminum alloy fin tube involved in each example.
[0075] (2) Corrosion resistance: The copper-aluminum alloy fin tubes are subjected to a salt spray corrosion resistance test at a test temperature of 35°C. A 5% mass concentration sodium chloride aqueous solution is sprayed in the test chamber to simulate accelerated corrosion in the environment. The copper-aluminum alloy fin tubes are qualified for corrosion resistance if their tolerance time (i.e., the time they remain rust-free) exceeds 1500 hours. Otherwise, they are unqualified.
[0076] (3) Thermal conductivity: The copper-aluminum alloy fin tube body involved in each example was tested for thermal conductivity; the test temperature was 80° C., referring to the standard GB / T 3651-2008.
[0077] (4) Fatigue resistance: The specimens were subjected to a constant amplitude fatigue test (maximum load 100 MPa, minimum load 20 MPa) on an Amsler HFP-422 high frequency fatigue testing machine, and the fatigue life was recorded and counted.
[0078] Table 1
[0079] project Tensile Strength Corrosion resistance Fatigue life Thermal conductivity unit MPa — Ten thousand times W / m·k Example 1 856 qualified 16.1 256 Example 2 860 qualified 16.3 259 Example 3 865 qualified 16.7 261 Example 4 868 qualified 16.8 266 Example 5 870 qualified 17.0 268 Comparative Example 1 821 Failure 15.8 253 Comparative Example 2 806 Failure 15.5 250
[0080] It can be seen from Table 1 that the copper-aluminum alloy fin tube disclosed in the embodiment of the present invention has better mechanical properties, corrosion resistance, fatigue resistance and thermal conductivity than the comparative example product. The addition of In, nano-tantalum silicide, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, Co, Na, nano-boron nitride and 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione is beneficial to improving the above properties.
[0081] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as described above. However, any technician familiar with the profession can make some changes, modifications and evolutions of the technical content disclosed above without departing from the scope of the technical solution of the present invention, which are all equivalent embodiments of the present invention. At the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A copper-aluminum alloy fin tube, characterized in that: The invention comprises a fin tube body and a functional coating coated on the surface thereof; the fin tube body is made of the following components in weight percentage: Mo 0.5-1.5wt%, Ag 0.01-0.03wt%, Nb0.1-0.3wt%, Co 0.2-0.6wt%, Hf 0.1-0.3wt%, rare earth elements 0.05-0.15wt%, Ni 0.01-0.12wt%, Zn0.3-0.5wt%, Si 0.3-0.6wt%, Be 0.005-0.015wt%, In 0.003-0.01wt%, Na0.001-0.003wt%, Al8-15wt%, nano boron fiber 0.01-0.03wt%, nano boron nitride 0.01-0.03wt%, nano tantalum silicide 0.005-0.012wt%, the balance is Cu; the functional coating is made of the following components calculated by weight: amino-terminated hyperbranched polysiloxane HPSi-NH2 40-50 parts, 1,3,5-triglycidyl-S-triazinetrione 3-5 parts, thermal conductive filler 10-15 parts, coupling agent 1-3 parts, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane 3-5 parts, 5,5-dimethyl-1,3-di(oxiranylmethyl)imidazolidine-2,4-dione 4-6 parts, solvent 60-80 parts.
2. The copper-aluminum alloy fin tube according to claim 1, characterized in that: The thickness of the functional coating is 50-100 microns.
3. The copper-aluminum alloy fin tube according to claim 1, characterized in that: The rare earth elements are a mixture of Sc, Y, La, and Ce in a mass ratio of 1:(1-2):(0.8-1.2):(1-1.5); the average diameter of the nano-boron fiber is 30-100nm, and the aspect ratio is (15-25):1; the particle size of the nano-boron nitride is 10-90nm; and the particle size of the nano-tantalum silicide is 20-80nm.
4. The copper-aluminum alloy fin tube according to claim 1, characterized in that: The solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.
5. The copper-aluminum alloy fin tube according to claim 1, characterized in that: The thermal conductive filler is at least one of aluminum nitride, boron nitride and silicon carbide; the particle size of the thermal conductive filler is 1200-1600 mesh.
6. The copper-aluminum alloy fin tube according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.
7. A production process for the copper-aluminum alloy finned tube according to any one of claims 1 to 6, characterized in that: The steps include: Step S1, vacuum metallurgy smelting, argon protection casting into a round billet, after homogenization treatment, hot extrusion into a rod, and then heat treatment to obtain a fin tube body; Step S2: after mixing the components of the functional coating evenly, apply the mixture on the surface of the fin tube body, and dry at 105-115° C. to a constant weight to obtain a copper-aluminum alloy fin tube.
8. The production process of the copper-aluminum alloy fin tube according to claim 7, characterized in that: The temperature of the homogenization treatment in step S1 is 800-830°C for 1-2 hours; the temperature of the hot extrusion is 630-650°C.
9. The production process of the copper-aluminum alloy fin tube according to claim 7, characterized in that: The heat treatment in step S2 includes solution treatment, aging treatment and annealing treatment; the temperature of the solution treatment is 550-580°C and the time is 3-5h; the temperature of the aging treatment is 190-240°C and the time is 4-6h; the annealing treatment is 630-730°C and the time is 2-4h.
Citation Information
Patent Citations
A copper-aluminum alloy finned tube
CN105758244B
A method for preparing amino-terminated hyperbranched polysiloxane-modified waterborne polyurethane
CN110156948B
Preparation process of rare-earth copper alloy material for preparing integral dispersion copper
CN101338389A
Aluminum bronze composite slide bearing material containing nanometer particles and grease and preparation method thereof
CN105063396A